Correction to: Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities - George, T. S.; Giles, C. D.; Menezes-Blackburn, D.; Condron, L. M.; Gama-Rodrigues, A. C.; Jaisi, D.; Lang, F.; Neal, A. L.; Stutter, M. I.; Almeida, D. S. [UNESP]; Bol, R.; Cabugao, K. G.; et al. (Springer Nature, 2018)
The article “Organic phosphorus in the terrestrial environment: a perspective on the state of the art and future priorities”, written by Timothy S George et al., was originally published with incorrect affiliation information for one of the co-authors, E. Klumpp.